Systematic Review and Meta-Analysis of the Evaluation of the Efficacy of Manipulation and Cervical Traction in the Treatment of Radical Cervical Spondylosis - Jianquan Chen; Rongbin Chen; Yong Li; Maoshui Chen; Zhouming Lv; Haobin Zeng; Qiang Lian (Emergency Medicine International)
Background. With the accelerated pace of life in modern society, changes in work style, and the popularity of computers, the prevalence of cervical spondylosis (CSR) is increasing, and the age of onset is advancing. Once suffering from this disease, it is often difficult to cure and recurring, with complex clinical symptoms, causing a serious impact on human health. Objective. To evaluate the efficacy of manipulation and cervical traction in the treatment of radical cervical spondylosis. Methods. The PubMed, CNKI, and Wanfang databases were searched for literature. The literature related to this study was included according to selective criteria and inhibitory elimination criteria, and valuable information was selected for statistical analysis, resulting in a total of 11 randomized controlled trials with 994 subjects. Results. The short-term efficacy of manual treatment for CSR was superior to that of cervical traction alone (P<0.05); subgroup analysis showed that the short-term efficacy of pulling or rotational manipulation was superior to that of cervical traction (P<0.05). The mean difference between symptoms and manipulation VAS scores was higher before and after treatment when compared with cervical traction for CSR (P<0.05); the subgroup analysis showed that VAS scores, upper extremity anesthesia scores, and survivorship scores were lower for pulling or rotating manipulation than for cervical traction (P<0.05). Conclusion. The advantages of manual therapy in terms of short-term efficacy, VAS pain scores, neck pain, upper extremity anesthesia, and survivorship improvement provide a theoretical basis for its clinical impact.